2019
DOI: 10.3892/ol.2019.10447
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase‑1 predicts overall survival outcomes in non‑small cell lung cancer patients treated with carboplatin and navelbine

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive lipid metabolite associated with cancer cell proliferation, survival, migration and regulation of tumor angiogenesis in various cellular and animal models. Sphingosine kinase-1 (SphK1) and S1P lyase are the main enzymes that respectively control the synthesis and degradation of S1P. The present study analyzed the prognostic and predictive value of SphK1 and S1P lyase expression in patients with non-small cell lung cancer (NSCLC), treated with either surgery alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…There are many examples of SK1 upregulation at the mRNA and protein level, which is often associated with poor prognosis including reduced survival and earlier disease recurrence in cancer patients [2]. Recent examples include melanoma [62], papillary thyroid carcinoma [84], non-small cell lung cancer [85], triple-negative breast cancer [86] and colorectal cancer [87]. This is consistent with the ability of SK1 to promote cell survival, proliferation and neoplastic transformation and supports the therapeutic potential of SK1 inhibitors.…”
Section: Sk1/sk2 and Cancermentioning
confidence: 57%
“…There are many examples of SK1 upregulation at the mRNA and protein level, which is often associated with poor prognosis including reduced survival and earlier disease recurrence in cancer patients [2]. Recent examples include melanoma [62], papillary thyroid carcinoma [84], non-small cell lung cancer [85], triple-negative breast cancer [86] and colorectal cancer [87]. This is consistent with the ability of SK1 to promote cell survival, proliferation and neoplastic transformation and supports the therapeutic potential of SK1 inhibitors.…”
Section: Sk1/sk2 and Cancermentioning
confidence: 57%
“… 43 Furthermore, it was reported that high SPHK1 expression is associated with shorter overall survival and increased risk of disease relapse in patients with NSCLC treated with adjuvant chemotherapy in recent study. 44 Ectopic expression of SPHK1 in NSCLC cells dramatically enhances their resistance to apoptosis induced by doxorubicin or docetaxel, 2 commonly used chemotherapeutics, whereas suppressing SPHK1 expression with small-hairpin RNAs or inhibiting SPHK1 activity with a specific SPHK1 inhibitor (SK1-I) markedly abrogated the ability of NSCLC cells to resist cytotoxic reagent-induced cell death, suggesting that SPHK1 activity contributes to sustaining the unwanted survival of NSCLC cells under the treatment of chemotherapeutics. In fact, injection of SK1-I potently enhanced the tumor suppression effect to docetaxel, a clinically well-established, proapoptotic chemotherapy drug against breast, ovarian, and NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Our functional enrichment analysis suggests that the genes in our prognostic signature are widely involved in the immune process. Among all the 21 prognostic genes, 14 (e.g., AQP3, BIRC5, C5AR1, HMOX1, IL32, IL6ST, MIF, MMP12, PLAUR , PMAIP1, RAC1, SMAD6, SPHK1, USP7) have been reported to be served as a prognostic biomarker or suggested to be a novel therapeutic targets for lung adenocarcinoma [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. The remaining 7 genes, including ARF6, C7, ELF4, ITPR1, MOV10, PTCH1 and RIPK2, have not been previously reported to be associated with LUAD prognosis and might act as potential biomarker.…”
Section: Discussionmentioning
confidence: 99%